Chapter 4 How a Behavioral Economic Framework Can Support Scaling of Early Childhood Interventions - Gennetian, Lisa A. (Taylor & Francis, 2021)
Combining the theories of conventional economics with social psychology and cognitive decision making, behavioral economics (BE) offers an interdisciplinary framework to support the transition and translation of programs to scale, addressing the dimensions of feasibility, cost, and fidelity while meeting the objectives of providing safe, nurturing, and stimulating environments for children. One strength of BE is that decision-making is not considered context free, thus directly addressing an oft-cited weakness of translating programs to scale. Insights from BE specifically on parent decision making related to choice structure, fear of judgment, miscalibration, and social norms can generate light-touch enhancements to foster success as interventions scale to that help parents access and digest information and follow through on intentions. Examples of successful applications of the BE lens to scaled home visiting and parenting programs are described.